Psychological changes in Africans with kidney disease in Ghana: a comparison of haemodialysis patients and patients with chronic kidney disease not on dialysis - Bioma, Vincent; Ganu, Vincent Jessey; Dey, Dzifa Ida; Yorke, Ernest; Adjei, Patrick; Mate-Kole, Michael; Mate-Kole, Charles C (African Journal of Nephrology, 2019)
Background: The prevalence of chronic kidney disease (CKD) is high in sub-Saharan Africa and affects the productive workforce. CKD has been associated with psychological problems such as anxiety and depression; however, there is little published information on the burden of psychological problems among the CKD population in African countries. Our study assessed psychological changes in two groups of patients, one group with end-stage renal disease receiving chronic haemodialysis, and a second with CKD not on dialysis. Methods: A cross-sectional study involving patients on chronic haemodialysis and patients with CKD stages 3–5 (the “CKD” patients) was conducted at the Renal Unit of the Korle-Bu Teaching Hospital in Accra, Ghana. One hundred and sixty-eight participants (82 CKD and 86 haemodialysis patients) were recruited. Demographic, clinical and laboratory information was captured, the Revised Quick Cognitive Screening Test (RQCST) was used to assess cognitive function and the Brief Symptoms Inventory-18 (BSI-18) was used to screen for anxiety, somatization and depression. Results: CKD patients were older than those on haemodialysis, with mean ages of 53.3 and 46.6 years, respectively. Two-thirds (113/167) were male. The median glomerular filtration rate (GFR) of the CKD patients was 21 mL/min/1.73 m2 (interquartile range 9–34). Most of the haemodialysis patients (78.6%) were receiving two sessions of haemodialysis per week and their mean kT/V was 1.16 ± 0.23. The RQCST global scores in the two groups of patients were similar, with almost 90% of haemodialysis patients and 85% of CKD patients obtaining scores above 50. Haemodialysis patients had better scores for immediate recall memory. The haemodialysis patients also had higher BSI-18 global scores than the CKD patients (mean of 0.83 vs 0.70, p = 0.033). Mean anxiety and somatization scores were also higher in the haemodialysis patients. Conclusions: Haemodialysis patients demonstrated higher anxiety and somatization scores than the CKD patients. Clinical psychological support should therefore be included in the treatment of our patients, and especially for those on chronic haemodialysis.